Free nutritious school meals: Effects on student well-being and learning - Dedy; Sudarwan Danim; Azizatul Khairi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Students in many parts of Indonesia continue to face challenges such as hunger, low concentration, and unequal access to adequate nutrition, which negatively affect learning readiness and academic engagement. This study examines the implementation of the Free Nutritious School Meal Program and its implications for student well-being and learning in a public vocational high school in Bengkulu City, Indonesia. The study addresses the urgency of understanding how school feeding policies are operationalized at the school level to respond to students' nutritional and learning needs. A qualitative descriptive approach was employed, with data collected through observations, semi-structured interviews, and document analysis. The study involved purposively selected participants, including school leaders, teachers, students, and parents. The findings indicate that the program has been implemented through structured stages of preparation, distribution, supervision, and evaluation, contributing to improved student energy levels, learning engagement, healthy behaviors, and discipline. However, challenges related to logistics, staffing, infrastructure, and communication with food providers were identified. The study recommends strengthening school management capacity, improving infrastructure, and developing evidence-based monitoring systems to enhance program sustainability and effectiveness.